The Evaluasi Kelayakan Pembangunan Rumah Sederhana Program Bantuan Stimulan Perumahan Swadaya: - - Ernawati, Ernawati; Latupeirissa, Josefine Ernestine; Bungin, Erni Rante (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2025)
The need for housing is increasing in line with population of Indonesia. Therefore, housing development needs to be encouraged for the sustainability of housing availability for the people, including Low-Income Communities. The construction of Simple Houses under the Bantuan Stimulan Perumahan Swadaya Program (BSPS) in Village